Role of sodium leak channel (NALCN) in sensation and pain: an overview - Zhang, Donghang; Wei, Yiyong (Frontiers in Pharmacology, 2024)
The sodium leak channel (NALCN) is widely expressed in the central nervous system and plays a pivotal role in regulating the resting membrane potential (RMP) by mediating the Na+ leak current. NALCN was first reported in 1999, and since then, increasing evidence has provided insights into the structure and functions of NALCN. As an essential component of neuronal background currents, NALCN has been shown to be involved in many important physiological functions, particularly in the respiratory rhythm, as NALCN mutant mice have a severely disrupted respiratory rhythm and die within 24 hours of birth. Many patients with NALCN mutations also develop serious clinical syndromes, such as severe hypotonia, speech impairment, and cognitive delay. Recently, emerging studies have clarified the human NALCN structure and revealed additional properties and functions of NALCN. For instance, accumulating evidence highlights that the NALCN is involved in normal sensation and pain. Here, we review the current literature and summarize the role of the NALCN in sensation and pain.